SISTEMATIK LITERATUR REVIEW SYSTEMATIC LITERATURE REVIEW: KEMAMPUAN BERPIKIR KRITIS MATEMATIS PADA MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFE) - Khunaeni, Sirilivia; Mastur, Zaenuri; Walid; Mariani, Scolastika; Hendikawati, Putriaji (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2023)
The purpose of writing this article is to explain the relationship between the Student Facilitator and Developing (SFE) learning model in mathematics learning and students' critical thinking abilities. The method used in this study is Literary Study. The literature study is carried out by searching various written sources, in the form of books, archives, magazines, articles and journals, or documents that are relevant to the problem being studied. By using 10 articles that have met the inclusion criteria, namely research subjects of middle school - high school students, meeting synta 1-4 and in the years 2013-2023. These articles were searched using national and international journal databases, namely Google Scholar, Garuda, Researchgate, Scopus and Science Direct. The findings showed that junior high school students' abilities in mathematical critical thinking skills were influenced after using the Student Facilitator and Developing (SFE) learning model. For further research, we can examine more broadly the use of the SFE model and its influence in critical mathematical thinking at various levels of educational units.